Prevalence and diversity of type VI secretion systems in a model beneficial symbiosis - Suria, Andrea M.; Smith, Stephanie; Speare, Lauren; Chen, Yuzhou; Chien, Iris; Clark, Emily Grace; Krueger, Madelyn; Warwick, Alexander M.; Wilkins, Hannah; Septer, Alecia N. (Frontiers in Microbiology, 2022)
The type VI secretion system (T6SS) is widely distributed in diverse bacterial species and habitats where it is required for interbacterial competition and interactions with eukaryotic cells. Previous work described the role of a T6SS in the beneficial symbiont, Vibrio fischeri, during colonization of the light organ of Euprymna scolopes squid. However, the prevalence and diversity of T6SSs found within the distinct symbiotic structures of this model host have not yet been determined. Here, we analyzed 73 genomes of isolates from squid light organs and accessory nidamental glands (ANGs) and 178 reference genomes. We found that the majority of these bacterial symbionts encode diverse T6SSs from four distinct classes, and most share homology with T6SSs from more distantly related species, including pathogens of animals and humans. These findings indicate that T6SSs with shared evolutionary histories can be integrated into the cellular systems of host-associated bacteria with different effects on host health. Furthermore, we found that one T6SS in V. fischeri is located within a genomic island with high genomic plasticity. Five distinct genomic island genotypes were identified, suggesting this region encodes diverse functional potential that natural selection can act on. Finally, analysis of newly described T6SSs in roseobacter clade ANG isolates revealed a novel predicted protein that appears to be a fusion of the TssB-TssC sheath components. This work underscores the importance of studying T6SSs in diverse organisms and natural habitats to better understand how T6SSs promote the propagation of bacterial populations and impact host health.